DEVELOPMENTS IN THE FIELD OF PRODUCTION OF CONTINUOUSLY CAST SLUGS OF COMPOUND CROSS-SECTION OF GREY AND HIGH-STRENGTH CAST IRON - V. S. Shumihin (Литьë и металлургия)
The joint works within the period of 1980–1985 of ITM NAN of Belarus, Institute of casting problems of AN Ukraine and Kaunas works «Tsentrolit» in the field of grey and high-strength cast iron hardening, developments of crystallizers constructions and technologies of production of ingots of compound cross- section by method of horizontal continuous casting, are described.